"A tale of two virtual communities": A preliminary analysis of discourse in two online programming support communities. Issue 1 (22nd October 2020) - Sengupta, Subhasree
Abstract: Software programming is increasingly becoming a collaborative and community driven effort, with online discussions becoming vital resources for learning and knowledge sharing. This study explores differences in the discourse patterns in two popular online programming communities to provide preliminary insights for the question of how virtual learning communities should be designed and structured. A content analysis of a random sample of 15 discussion threads from each of r/Askprogramming (236 contributions) and Stack Overflow (SO; 224 contributions) was used to explore the observed interaction patterns. Differences between sites emerge in the scope of topics and the nature of responses the community provides. While Stack Overflow is more task‐specific, r/Askprogramming supports a greater sense of bonding and camaraderie among community members in addition to task‐specific discussions. These findings suggest key normative structures that regulate the nature of discourse in these communities which may in turn have design implications for such online learning initiatives.